1993
DOI: 10.1113/jphysiol.1993.sp019681
|View full text |Cite
|
Sign up to set email alerts
|

Calcium release‐activated calcium current in rat mast cells.

Abstract: SUMMARY1. Whole-cell patch clamp recordings of membrane currents and fura-2 measurements of free intracellular calcium concentration ([Ca21]i) were used to study the biophysical properties of a calcium current activated by depletion of intracellular calcium stores in rat peritoneal mast cells.2. Calcium influx through an inward calcium release-activated calcium current (ICRAC) was induced by three independent mechanisms that result in store depletion: 6. The selectivity of 'CRAC for Ca2+ was assessed by using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

51
698
6
1

Year Published

1996
1996
2007
2007

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 709 publications
(756 citation statements)
references
References 39 publications
51
698
6
1
Order By: Relevance
“…Previously we showed that ICRAC in mast cells was reduced by 9 + 2% (n = 4) when replacing external Na + and K + by Nmethyl-D-glucamine (membrane potential -40 mV [14]). A reduction of 10.9 + 6.1% (n = 6) was also seen at more negative potentials (-82 mV) indicating the voltage independence of this reduction.…”
Section: Resultsmentioning
confidence: 92%
See 4 more Smart Citations
“…Previously we showed that ICRAC in mast cells was reduced by 9 + 2% (n = 4) when replacing external Na + and K + by Nmethyl-D-glucamine (membrane potential -40 mV [14]). A reduction of 10.9 + 6.1% (n = 6) was also seen at more negative potentials (-82 mV) indicating the voltage independence of this reduction.…”
Section: Resultsmentioning
confidence: 92%
“…However, if one compares the data published on permeation and selectivity for both channel types, it becomes clear that CRAC and trp are not identical. The Ca z+ selectivity over monovalent cations for CRAC channels in mast, RBL, and Jurkat T-cells was found to be 1000/1 or greater [14,15] whereas for trp it is about 40/1 [11]. Comparing the endogenous insect SOC channels with expressed trp channels in Sf9 cells, Vaca et al [29] showed that this SOC channel and the trp channel were clearly different regarding the permeation properties of Ca 2+, Ba 2+, Mg 2+, and Na +.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations